From Triboelectric Nanogenerator to Uninterrupted Power Supply System: The Key Role of Electrochemical Batteries and Supercapacitors - Yajun Mi; Yin Lu; Xueqing Wang; Zequan Zhao; Xia Cao; Ning Wang (Batteries, 2022)
Currently, significant advances have been made in the field of high-performance energy storage technologies, such as Li-ion batteries and supercapacitors. However, the limited lifespans, as well as the frequent charging or replacement requirements, pose a set of challenges for their application in the Internet of things (IoTs), because the full power of the IoTs can only be realized by the sustainable operation of physical objects, especially embedded sensors, for the purpose of connecting and exchanging data with other devices and systems continually in real-time. A viable option for achieving the sustainability of the IoTs may be the combination of renewable energy harvesting technologies such as triboelectric nanogenerators (TENGs) with electrochemical energy storage technologies, where TENGs can harvest mechanical energies from ambient environments and transform them into electricity for charging electrochemical batteries and supercapacitors (SCs) conveniently, thus developing a new type of TENG-based uninterrupted power supply (TENG-UPS). In this review, we begin from a brief description of the operating mode of TENG and the integration strategy of TENG-UPS. The latest advances in the TENG-UPS are then thoroughly discussed from the perspective of structural design and system integration. Cutting edge developments of the as-designed self-powered sensing systems are then concisely illustrated to disclose the application potential in the IoTs. The main obstacles and future prospects for developing TENG-UPS-based intelligent systems are also highlighted in terms of design and manufacture at the conclusion. We expect this review will appropriately shine a light on the understanding of the key role of electrochemical energy storage devices in the development of TENG-based energy harvesting technology as well as the self-powered intelligent systems.